The Integration of Fintech and Banks: A Balancing Act Between Risk and Opportunity - Magdy, Mohamed; Raouf, Engy; Al-wakeel, Nashaat (International Journal of Membrane Science and Technology, 2023)
Financial technology is a widely discussed issue in industrialized countries, although it is relatively new in underdeveloped ones. With the emergence of financial technology (fintech), the banking sector has undergone significant changes. This paper investigates the impact of fintech, both inside and outside the industry (startups), on the profitability of the banking sector. Using a panel of eighteen Egyptian banks over the period 2017 -2021, the study employs a panel fixed effect, a generalized method of the moment and robust least squares models to examine the relationship between fintech and bank profitability. Our findings reveal a significant relationship between fintech and bank profitability, suggesting that the adoption of fintech inside the banking sector has a negative effect on bank profitability, while the adoption of fintech outside the banking sector has a positive and significant effect on bank profitability. These findings have significant implications for policymakers and industry stakeholders as they navigate the evolving financial landscape.